Plant Puzzle: How to Apply It to Increase Children's Interest in Learning Science? - Jelita, Jelita; Syarfina, Syarfina; Fadhila, Novia (Universitas Nahdlatul Ulama Surabaya, 2022)
Learning science concerning early childhood should focus on a fun learning process. However, children's interest in learning while participating in the science learning process is still low; some children are busy playing alone, disturbing their friends, doing other work, and going in and out for various reasons when science learning occurs. This study aims to increase children's interest in learning science through plant puzzle media. The research used the Classroom Action Research (CAR) with the Kemmis-Taggart model with four stages: plan, implementation, observation, and reflection. The participants are ten children aged 5-6 years at Al Faiz Early Childhood Education (ECE) Langsa, Aceh. The researcher used an observation sheet with four indicators: interest in learning, attention to learning, motivation, and knowledge to obtain improvement data. The results showed an increased children's interest in learning science in each cycle. The average score of children in the Well Developed (WD) category was 76%. In addition, children's activities also showed outstanding improvement during the teaching and learning process. The researcher concluded that plant puzzle media could increase children's interest in learning science. The implication of research related to the effectiveness of plant puzzle media on learning other than science needs to be studied further.